Web Accessibility Challenges - Hayfa.Y.Abuaddous; Mohd Zalisham Jali; Nurlida Basir (The Science and Information (SAI) Organization Limited, 2024)
(IJACSA) International Journal of Advanced Computer Science and Applications, Vol. 7, No. 10, 2016